2022
DOI: 10.1002/btm2.10387
|View full text |Cite
|
Sign up to set email alerts
|

Needle to needle robot‐assisted manufacture of cell therapy products

Abstract: Advanced therapeutic medicinal products (ATMPs) have emerged as novel therapies for untreatable diseases, generating the need for large volumes of high‐quality, clinically‐compliant GMP cells to replace costly, high‐risk and limited scale manual expansion processes. We present the design of a fully automated, robot‐assisted platform incorporating the use of multiliter stirred tank bioreactors for scalable production of adherent human stem cells. The design addresses a needle‐to‐needle closed process incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…To date the adoption of robotics for cell therapy and regenerative medicine applications has been carried out for the expansion of single cell populations such as adult MSC expanded in bioreactor systems (34). Moreover, robotic based expansion and differentiation to induced pluripotent stem (IPS) cells towards retinal pigment epithelial cells showed a high level of cell purity and functionality (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date the adoption of robotics for cell therapy and regenerative medicine applications has been carried out for the expansion of single cell populations such as adult MSC expanded in bioreactor systems (34). Moreover, robotic based expansion and differentiation to induced pluripotent stem (IPS) cells towards retinal pigment epithelial cells showed a high level of cell purity and functionality (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…A well-characterised process and manufacturing line is imperative towards a successful translation (Rousseau et al, 2018, ten Ham et al, 2018. Significant progress has been made in automated cell culture, passaging and organoid seeding (31)(32)(33)(34), showing the feasibility and advantages of automating manual processes. Furthermore, robotic platforms using microtissues to create complex tissue constructs are appearing (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…For the development of an advanced therapy medicinal product (ATMP), reproducible quality has to be assured to meet the quality-related regulation requirements. For personalized treatment, it is mandatory to define optimal stem cell expansion and differentiation protocols, for example, to create iPSCderived patient-specific therapies, such as allogeneic cardiomyocyte patches, joint implants, and CAR-T-cell therapy [28,58] To enable large-scale cell production and clinically GMP-compliant manufacturing, stirred bioreactor-based platforms have been established to expand and differentiate MSCs and iPSCs under controlled conditions, [57,71,72] for example, to produce iPSC-derived hematopoietic cells [73] and cardiomyocytes. [74] Bioreactor-derived ) Initial epithelial tissue models such as those from (i) the airway epithelia and (ii) skin, have shown that these models require complex environments that include interfaces and other forces such as flow.…”
Section: Automated and Standardized Cell Culturementioning
confidence: 99%
“…These standardized production platforms avoid batch deviations and can enable reproducible and quality-assured cell cultures. [57][58][59] Stem cell factories, as they are known, have successfully been used to generate and expand iPSCs using defined and userindependent conditions with the economic advantage of a fully automated stem cell production and increased throughput. [59][60][61][62] As such, the integration of deep-learning-based algorithms into robotic pipelines has resulted in noninvasive routine assessment of iPSCs, concerted by the use of fluorescent reporter lines, to ascertain a standardized protocol for monitoring, e.g., the proliferation rate and cell confluency prior to splitting cells and further propagation.…”
Section: Automated and Standardized Cell Culturementioning
confidence: 99%
“…Development and use of bio-inspired, fabricated bio-printed constructs will require validated and relevant cell sources and/or use of appropriate factors to attract endogenous stem cells to the constructs. The cost of producing GMP-grade MSCs, or even iMSCs, using manual processes is such that translation to patient use at scale to enable widespread use is prohibitive and a critical impediment in the field as noted by the group of M. Murphy* ( Ochs et al, 2022 ). The automation of production of advanced therapy medicinal products (ATMPs), state-of-the-art medicines for human use based on genes, tissues or cell-derived EVs can address this hurdle to clinical translation as reported by the group of M. Murphy* ( Ochs et al, 2022 ).…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%